THE BELOVED COMMUNITY IN SHAW: CONSTRUCTING NARRATIVE IDENTITY IN THE ANTI-GENTRIFICATION MOVEMENT - Graves, Shelley Allison (Wake Forest University, 2009)
The grounds of social movements have long been fertile for the construction of value making narratives. Social movements rely heavily on the publicly acknowledged moral value of their causes for legitimacy, values often cultivated through identification with existing community beliefs. Likewise, Fisher’s paradigm teaches us that narratives are not constantly brand new; they are instead validated and defined in their archetypal elements and in the values those archetypes have repetitively taught us. Scholars of rhetoric seek to develop schemata for the classification of social movements. My goal is to determine the goals of the anti-gentrification movement and to investigate how those goals are articulated and validated through narration. Specifically I examine the power of the beloved community narrative as an organizing force in the anti-gentrification movement.
Keywords: gentrification; social movement; beloved community; Shaw neighborhood; narrative; community organizing